2022
DOI: 10.1093/police/paac061
|View full text |Cite
|
Sign up to set email alerts
|

Reducing agency and social costs by keeping kids in school and out of the justice system: A cost–benefit analysis of the Philadelphia Police School Diversion Program

Abstract: Growing recognition of the school-to-prison pipeline and its associated detrimental effects has spurred efforts aimed at reducing the rate of school-based arrests across the United States. One such initiative, the Philadelphia Police School Diversion Program, has demonstrated promising findings related to reduced numbers of school-based arrests and improved school outcomes among youth. However, without information about the financial costs and benefits associated with program operation, stakeholders may be hes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The primary goal of the Philadelphia Police School Diversion Program was to reduce school-based arrests across the city, and the annual number of school-based arrests in Philadelphia decreased by 84% by the fifth year of program operation (Goldstein, Kreimer, et al, 2021). Additionally, a cost–benefit analysis indicated that the program has produced a considerable net financial benefit, including an annual taxpayer-supported cost savings of approximately $1.9 million in its fifth year of operation (NeMoyer et al, 2022). Regarding subsequent outcomes, diversion has been linked to a significant reduction in suspension outcomes over a 1-year follow-up period (Goldstein, NeMoyer, et al, 2021) and a significant, yet small, reduction in recidivism arrests over a 5-year follow-up period, but no significant school-related impacts over a 4-year follow-up period (the current study).…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of the Philadelphia Police School Diversion Program was to reduce school-based arrests across the city, and the annual number of school-based arrests in Philadelphia decreased by 84% by the fifth year of program operation (Goldstein, Kreimer, et al, 2021). Additionally, a cost–benefit analysis indicated that the program has produced a considerable net financial benefit, including an annual taxpayer-supported cost savings of approximately $1.9 million in its fifth year of operation (NeMoyer et al, 2022). Regarding subsequent outcomes, diversion has been linked to a significant reduction in suspension outcomes over a 1-year follow-up period (Goldstein, NeMoyer, et al, 2021) and a significant, yet small, reduction in recidivism arrests over a 5-year follow-up period, but no significant school-related impacts over a 4-year follow-up period (the current study).…”
Section: Discussionmentioning
confidence: 99%